Recent application of linear analysis techniques - Gibbard, M J; Martins, N; Sanchez-Gasca, J J; Uchida, N; Vittal, V; Wang, L (IEEE transactions on power systems, 2001)
The subjects discussed by the panelists at the Panel Session: Recent Applications of Linear Analysis Techniques conducted during the 1998 IEEE PES Summer Meeting are discussed. The subjects include control system design, system identification and large scale system applications. Linear analysis techniques are used to a broad range of power system performance issues.